Estimation of competitive activity in synchronized swimming - Shulga, L. M.; Rudkovskaya, T. I. (Physical Education of Students, 2013)
Aim - is to develop the approach to technical complexity estimation of free routine composition in synchronized swimming. Were analyzed and considered free routine compositions of the strongest swimmers in European and World Championships during the period under study (2008-2011). In the research took part 32 qualified athletes different ages. Were determined the options of the constructed of free program and location the combination saturation in those programs. Were established complicated elements distribution by the minutes of the free routine composition performance and developed the approach to technical complexity estimation of free routine composition (solo) for using in training and competitive activity for qualified athletes in synchronized swimming. The total time of breath-holding makes up 40% of the time of the whole free routine composition.